Don't Judge a Book by Its Cover: Factitious Disorder Imposed on Children-Report on 2 Cases - Faedda, Noemi; Baglioni, Valentina; Natalucci, Giulia; Ardizzone, Ignazio; Camuffo, Mauro; Cerutti, Rita; Guidetti, Vincenzo (Frontiers in Pediatrics, 2018)
Factitious Disorder Imposed on Another (FDIA), also known as Munchausen Syndrome by Proxy (MSbP) is a very serious form of child abuse. The perpetrator, usually the mother, invents symptoms or causes real ones in order to make her child appear sick. Usually this is due to a maladaptive disorder or to an excessive of attention-seeking on her part. We report here two new cases of FDIA. The first one is a 9-year-old boy with a history of convulsive episodes, reduced verbal production, mild psychomotor disorder and urological problems who underwent several invasive procedures and hospitalizations before a diagnosis of FDIA was made. The second is a 12 year-old girl with headache, abdominal pain, lipothymic episodes, seizures and a gait impairment, who was hospitalized in several hospitals before an FDIA was diagnosed.